Comparison of weight estimation formulae in paediatric patients at Chris Hani Baragwanath Academic Hospital - Soni, Zakiyya (My University, 2018)
Background Accurate weight determination is essential in providing optimal care to the paediatric population, as both over- and under-estimation can be detrimental. This study aimed to compare the accuracy and precision of three paediatric weight estimation formulae, the Advanced Paediatric Life support (APLS), the formula used by anaesthetists in academic hospitals affiliated to the University of Witwatersrand (Wits-A), and the Luscombe and Owens (LO) formula, to the measured weight of children at the Chris Hani Baragwanath Academic Hospital (CHBAH) outpatient department. Methods A prospective, contextual, descriptive study design was used with quota sampling. Four hundred children aged 1 - 10 years were recruited for the study. Age, gender, ethnicity, weight and height were recorded. Results On average the APLS formula performed the best with 49 % of estimates within 10% of the actual measured weight (PW10), the lowest mean percentage difference (MPD) of +0.7% and the narrowest 95% limits of agreement. The Wits-A formula followed with a PW10 of 41% and a MPD of -5.2% while the LO formula had a PW10 of 24% and a MPD of -19.4%. Conclusion An accurate and precise weight estimation technique remains elusive and the gold standard is a measured weight. The APLS formula was however found to be the most accurate in the CHBAH population and should be used over the Wits-A formula if a formula has to be used.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2017.
Keywords: Pediatric Weight Estimated Formula; Pediatrics